Mitochondrial Contribution to the Anoxic Ca(2+) Signal in Maize Suspension-Cultured Cells - Subbaiah, Chalivendra C. (American Society of Plant Physiologists, 1998)
Anoxia induces a rapid elevation of the cytosolic Ca(2+) concentration ([Ca(2+)](cyt)) in maize (Zea mays L.) cells, which is caused by the release of the ion from intracellular stores. This anoxic Ca(2+) release is important for gene activation and survival in O(2)-deprived maize seedlings and cells. In this study we examined the contribution of mitochondrial Ca(2+) to the anoxic [Ca(2+)](cyt) elevation in maize cells. Imaging of intramitochondrial Ca(2+) levels showed that a majority of mitochondria released their Ca(2+) in response to anoxia and took up Ca(2+) upon reoxygenation. We also investigated whether the mitochondrial Ca(2+) release contributed to the increase in [Ca(2+)](cyt) under anoxia. Analysis of the spatial association between anoxic [Ca(2+)](cyt) changes and the distribution of mitochondrial and other intracellular Ca(2+) stores revealed that the largest [Ca(2+)](cyt) increases occurred close to mitochondria and away from the tonoplast. In addition, carbonylcyanide p-trifluoromethoxyphenyl hydrazone treatment depolarized mitochondria and caused a mild elevation of [Ca(2+)](cyt) under aerobic conditions but prevented a [Ca(2+)](cyt) increase in response to a subsequent anoxic pulse. These results suggest that mitochondria play an important role in the anoxic elevation of [Ca(2+)](cyt) and participate in the signaling of O(2) deprivation.